The Cost of Job Security Regulation: Evidence from Latin American Labor Markets - Carmen Pagés-Serra; James J. Heckman (Inter-American Development Bank, Research Department, 2000)
This paper documents the high level of job security protection in Latin American labor markets and analyzes its impacts on employment. The authors show that job security policies have a substantial impact on the level and the distribution of employment in Latin America. These policies reduce employment and promote inequality. The institutional organization of the labor market affects both employment and inequality.
Keywords: 330; Beschäftigungssicherung; Erwerbstätigkeit; Lateinamerika